Tools to tipple: ethanol ingestion by wild chimpanzees using leaf-sponges - Hockings, K; Bryson-Morrison, N; Carvalho, S; Fujisawa, M; Humle, T; McGrew, W; Nakamura, M; Ohashi, G; Yamanashi, Y; Yamakoshi, G; Matsuzawa, T (Royal Society, 2015)
African apes and humans share a genetic mutation that enables them to effectively metabolize ethanol. However, voluntary ethanol consumption in this evolutionary radiation is documented only in modern humans. Here, we report evidence of the long-term and recurrent ingestion of ethanol from the raffia palm (Raphia hookeri, Arecaceae) by wild chimpanzees (Pan troglodytes verus) at Bossou in Guinea, West Africa, from 1995 to 2012. Chimpanzees at Bossou ingest this alcoholic beverage, often in large quantities, despite an average presence of ethanol of 3.1% alcohol by volume (ABV) and up to 6.9% ABV. Local people tap raffia palms and the sap collects in plastic containers, and chimpanzees use elementary technology—a leafy tool—to obtain this fermenting sap. These data show that ethanol does not act as a deterrent to feeding in this community of wild apes, supporting the idea that the last common ancestor of living African apes and modern humans was not averse to ingesting foods containing ethanol.